Human resource development (HRD): Technology and ICT adoption in industrial sector, Malaysia - Md Dahalin, Zulkhairi; Ali, Juhary; Segumpan, Reynaldo G.; Abdullah, Rizal Zuhairi; Siraj, Fadzilah; Mat Junoh, Mohd Zukime; Ahmad, Ismail (Universiti Utara Malaysia, 2006)
The roles of information and communication technology (ICT) in boosting productivity and in promoting human resource development cannot be underestimated. Small and medium enterprises, in particular, have to grapple with the technological innovations that challenge operations, efficiency, and productivity vis-à-vis human resource capabilities.As in many countries, Malaysia has adopted ICT in various sectors such as manufacturing, banking, finance, and telecommunication, to name a few.These sectors utilize knowledge workers that have technological and ICT skills for competitive advantage.In line with the 9th Malaysia Plan (2006-2010), it was reported that investment from the technology and ICT sector are expected to be the main driver for the manufacturing sector’s overall growth, which in turn, could contribute to greater export and create more employment opportunities.This research assessed the development of human resources based on the application of ICT in the industrial sector in Malaysia.This was a field study in the form of a survey research using a random sample of organizations representing the industrial and government sectors in Malaysia. A total of 706 firms were selected in which questionnaires were sent and 120 usable returns were received representing a 17% response.The distribution of the sample suggests a high concentration of the ICT industry and high technology industry in the central and northern regions of Malaysia.Results of the study showed a moderate number of employees using IT were present in the organizations with more than half of the sample reported having employees with IT skills.There was also a low degree of technology and IT adoption among the sample with only half invested in technology and/or IT. Finally, the findings indicated that ICT adoption had a strong significant impact on the company’s productivity and quality of services.